Sufficiency Economy based Community Development Management for Reducing Inequality among the Poor Households - Phukamchanoad, Phusit (วารสารสันติศึกษาปริทรรศน์ มจร, 2019)
This research aims to analyze the level of community development management towards the participation in social inequality mitigation, relevant activities and the application of the sufficiency economy philosophy by both individuals and households. The data was collected by the use of questionnaires with 1,200 samples as well as interviews with 20 community leaders from the sufficiency economy-based model villages in three poorest provinces in the northern region: Maehongsorn, Prae and Nan. The research results showed that strong household leaders participated in the community development management for mitigating social inequality at high level. They also received direct benefits from the activities under the village development projects organized by the public sector. In addition, they were proud of the fact that their villages, families, neighbors and the public as a whole engaged in the conducted activities at high level. In terms of practicing sufficiency economy-based activities individuals and in households, such practice was rated at high level in overall and by indicators, especially in regard to natural resources preservation and common sufficient way of living. The application of the sufficiency economy philosophy by both individuals and their households was executed at high level, mentally in particular. They believed in the philosophy which suited them. They did not exploit others, and were satisfied with their sufficient way of life. They could genuinely synthesize the participatory society of happiness towards the participation process for creating a pleasant society based on the sufficiency economy philosophy—“Rectangular Ridge Model of Sufficiency” which simultaneously adheres to both nature and Buddhism.